Proceedings of the Joint Conference of the 47th Annual Meeting of the ACL and the 4th International Joint Conference on Natural 2009
DOI: 10.3115/1687878.1687912
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing stances in online debates

Abstract: This paper presents an unsupervised opinion analysis method for debate-side classification, i.e., recognizing which stance a person is taking in an online debate. In order to handle the complexities of this genre, we mine the web to learn associations that are indicative of opinion stances in debates. We combine this knowledge with discourse information, and formulate the debate side classification task as an Integer Linear Programming problem. Our results show that our method is substantially better than chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
320
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(329 citation statements)
references
References 21 publications
(27 reference statements)
3
320
0
6
Order By: Relevance
“…Somasundaran and Wiebe (2009) noticed that in online debate posts, people debate issues, express their favorites, oppose other stances, and argue why their thoughts are correct. To determine positive sentiment about one target, expressing negative sentiment about the other side is a key target.…”
Section: Related Workmentioning
confidence: 99%
“…Somasundaran and Wiebe (2009) noticed that in online debate posts, people debate issues, express their favorites, oppose other stances, and argue why their thoughts are correct. To determine positive sentiment about one target, expressing negative sentiment about the other side is a key target.…”
Section: Related Workmentioning
confidence: 99%
“…The first studies on stance detection and classification from a computational perspective used data derived from ideological online debates (Somasundaran and Wiebe 2010). They created a lexicon with positive and negative entries, and showed that the sentiment-and argument-based systems outperform the baseline ones in overall accuracy (63.93 %).…”
Section: Computational Approaches To Stance Identificationmentioning
confidence: 99%
“…Supervised learning has been used in almost all of the current approaches for stance classification, in which a large set of data has been collected and annotated in order to be used as training data for classifiers. In (Somasundaran and Wiebe, 2010), a lexicon for detecting argument trigger expressions was created and subsequently leveraged to identify arguments.…”
Section: Related Workmentioning
confidence: 99%
“…A related older strand of research (that uses the term 'argumentative structure' in a related but different sense than ours) has investigated automatically classifying the sentences of a scientific article's abstract or full text in terms of their contribution of new knowledge to a field (e.g., Liakata et al 2012, Teufel 2010, Mizuta et al 2005). In addition, argumentation mining has ties to sentiment analysis (e.g., Somasundaran and Wiebe 2010). To date there are few corpora with annotations for argumentation mining research ) although corpora with annotations for argument sub-components have recently become available (e.g., .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation